Milking machine and udder health management factors associated with bulk milk somatic cell count in Uruguayan herds - Vissio, Claudina (2018)
This paper describes the findings of static milking machine tests and milking observations on Uruguayan dairy farms. The aim of this study was to investigate the association between both milking machine performance and udder health management factors and bulk milk somatic cell count (BMSCC) in Uruguayan dairy herds. Data from 907 visits were used for the analysis. The farm visits were made between April 2006 and November 2015 and farms were located in 17 of the 19 departments of Uruguay. Each visit involved a short static machine test and observation of the milking process; the use of blanket dry cow therapy was also recorded. The BMSCC was the variable of interest. Univariable analysis was applied to explore the best set of predictors to be included in the multivariable model. A multivariable linear regression model was fitted. The median BMSCC over the years was 376 thousand cells/mL (interquartile range = 280,000–500,000 cells/mL). The final model showed a lower BMSCC for herds that used post-milking teat disinfection, applied the teat cups to dry teats and maintained the pulsation system in good working order. There was no significant association between BMSCC and blanket dry cow therapy in the final model. The association of these milking machine and udder health management factors with the BMSCC under Uruguayan conditions is relevant information for a dairy industry that needs low BMSCCs to compete on the world market.